Effects of aerobic, resistance, interval, and combined training on glucose metabolism in older adults: insights into type, dose, and mechanism - Zhang, Qilong; Guo, Yifan; Zhang, Hengyi; Xu, Weiliang; Yin, Lijun (Frontiers in Physiology, 2025)
Aging is accompanied by reduced skeletal muscle insulin sensitivity, abnormal fat redistribution, and a gradual decline in pancreatic β-cell function, leading to impaired glucose homeostasis and an increased risk of type 2 diabetes mellitus and related complications. Exercise is widely recognized as a core non-pharmacological strategy to improve glucose metabolism in older adults. This is a narrative review based on a comprehensive search of PubMed and Web of Science databases up to September 2025. We summarize current evidence on the effectiveness of different exercise modalities—including aerobic, resistance, high-intensity interval, and combined training—in ameliorating age-related glucose metabolism disorders. Evidence suggests that, in the long term, combined training yields more comprehensive improvements in insulin secretion and multiple metabolic markers compared with single-modality interventions. Particular attention is given to the intensity, frequency, and duration of exercise interventions to discuss dose–response characteristics and practical implications for older adults. Mechanistic insights indicate that exercise exerts its benefits through multiple pathways, including enhanced skeletal muscle GLUT4 expression and mitochondrial function, reduced visceral and ectopic adiposity, suppression of chronic low-grade inflammation, and improved β-cell insulin secretion. Future research should focus on large-scale, long-term clinical trials and mechanistic studies to refine exercise prescriptions, clarify dose–response relationships, and characterize the unique metabolic adaptations of the elderly population.